Three new species of Lichomolgella Sars G.O., 1918 (Copepoda, Cyclopoida, Sabelliphilidae) associated with Bryozoa in Korea - Jimin Lee; Il-Hoi Kim (ZooKeys)
Three new species of Lichomolgella Sars G.O., 1918 are described as associates of bryozoan hosts from Korea. In all three species, the endopod of leg 1 is two-segmented, unlike the two previously known species of this genus. As additional diagnostic features, L. exigua sp. nov. has a two-segmented endopod in legs 2 and 3, L. collata sp. nov. has one claw plus two setae on the third segment of the antenna and an inner coxal seta on legs 2 and 3, and L. nudicoxa sp. nov. lacks an inner coxal seta on all swimming legs. The genus Lichomolgella is transferred from the family Lichomolgidae to Sabelliphilidae and can be characterized by several diagnostic features, such as a claw in addition to setae on the second endopodal segment of the antenna, a single-segmented endopod of leg 4 bearing two distal spines, three spines plus five setae on the third exopodal segment of legs 3 and 4, a claw-like proximal scale on the mandibular gnathobase, and a vestigial distal lash of maxilla.